Risk of herpes simplex keratitis recurrence after ocular surgeries - Kanclerz, Piotr; Przewłócka, Katarzyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
The prevalence of herpesvirus types 1 and 2 rises with age, affecting up to 40% of adults in Europe. A proportion of these individuals may develop herpes simplex keratitis, most commonly due to secondary infection, i.e. via a ganglionic reaction and axoplasmic flow that transports the virus to the ocular surface. In patients with a history of ocular herpes infection, any ophthalmic procedure significantly elevates the risk of recurrence. The aim of the study was to analyze factors contributing to HSV reactivation following ophthalmic surgery and to explore potential preventive strategies. Reactivation of the HSV can be triggered by damage to the corneal neural plexus resulting from surgical manipulation, as well as by a localized suppression of immune activity caused by perioperative steroid therapy. Postoperative herpes keratitis has been reported after various procedures, including cataract surgery, vitrectomy, photokeratorefractive surgeries, and corneal transplants. Oral prophylaxis can help minimize the risk of recurrence and decrease the likelihood of transplant rejection in patients with herpes keratitis who have undergone penetrating keratoplasty. Studies indicate that oral acyclovir therapy (400 mg twice daily) is more effective compared to topical treatments. For non-keratoplasty ophthalmic procedures, it is advisable to delay surgery until at least three months after inflammatory activity has subsided and to consider oral prophylaxis in the perioperative period.